Gaya Seni Arca Masa Kᾱḍiri: Studi Terhadap Arca Candi Gurah dan Candi Tondowongso - Sukawati Susetyo; Ashar Murdihastomo; Agustijanto Indradjaja; Dimas Nugroho (KALPATARU, 2021)
In the archaeology Hindu-Buddhist era in Indonesia, there are several known art styles temple building architecture and statue art: Early Classical Era and Late Classical Era. In more detail, that several eras can be described that Early Classical Era developed during the Old Mātaram era with the center of its reign at Central Java, and Late Classical Era Style developed during Kāḍiri/Siŋhasāri and Majapahit with the center of its reign at East Java. Late Classical Era Style divided into two subs, Kāḍiri/Siŋhasāri and Majapahit. Kāḍiri as an early dynasty in East Java not yet known clearly what the special characteristic style of its temple is building architecture and its statue art, and only been told that the Kāḍiri Era Style is the connecting line between Early Classical Era Style and Late Classical Era. This essay intends to find out special characteristics of the Kāḍiri Era Style (transition art style). For this reason, the research was carried out on statues comes from Gurah Temple and Tondowongso Temple, both temples knew the date, with relative dating method or absolute dating method. From this iconographic research in detail will describe parts of the statues, from then will obtain several features that always appear, and that’s characteristics are considered as a strong characteristic from statues from Kāḍiri Era Style.